Bibliopsychology, Bibliopedagogics, Bibliotherapy: History, Theory, Practice - Karpova, Nataliya L. (2016)
The article examines historical and practical issues of bibliopsychology and leading theoretical principles of the founder of psychology of reading – N.A.Rubakin. The basics and functions of bibliopedagogics are described and some data from history, theory and practice of bibliotherapy are outlined. Concrete experience of using bibliotherapy in logopsychotherapy is presented. The article contains a review of collective studies in the area of bibliopsychology, bibliopedagogics, bibliotherapy (2005, 2014) and also refers to the Reader of Studies on Reading and Literacy (2014) prepared by members of the Institute of Psychology, Russian Academy of Education.
Keywords: theory; methods; author; bibliotherapy; bibliopsychology; bibliopedagogics; text; reader